(untitled) (Journal of Tropical Resources and Sustainable Science (JTRSS), 2025)
Sulaman Lake is located in Tuaran-Kota Belud, Sabah is an important wetland area that supports rich mangrove ecosystems and provides resources for nearby communities. This study aimed to document and compare the diversity of mangrove species found across four zones which are Sulaman Lake, Sungai Kindu, Kampung Serusop, and Sungai Betutai. A total of 24 mangrove species were identified throughout this floral survey consisting of 12 exclusive and 12 associate mangrove species. Kampung Serusop was noted for having the greatest number of mangrove species found (18 species), followed by Sungai Betutai (19 species), Sungai Kindu (7 species), and Sulaman Lake (5 species). The Rhizophoraceae family was the most dominant and widely distributed particularly Rhizophora apiculata, R. mucronata, and Bruguiera gymnorhiza, which thrive in areas with strong tidal impact. The differences between exclusive and associate species reflected distinct zonation patterns, likely influenced by tidal changes and surrounding habitat features. All recorded species were listed as Least Concern by the IUCN. Overall, the findings highlight Sulaman Lake as a valuable and biodiverse mangrove habitat.